VICARIOUS MEMORIES: DO THEY PERFORM THE SAME JOB IN DIFFERENT CULTURAL MINDS? - Nourkova, V. V. (Modern Psychology, 2019)
Vicarious memories are recollections of events that happened to other people. They were recently recognized as a meaningful component of personal life story. In this study we examined whether vicarious memories were more common in collectivistic than in individualistic cultures and speculated that they might serve different functions in different cultural contexts. 323 participants with Chinese (N=89), Russian (N=142), and Uzbek (N=92) background drew a lifeline of their childhood. In general, females produced more vicarious lifelines than males and the Chinese participants produced more vicarious lifelines than their Russian and Uzbek female counterparts. The Uzbek male participants generated the least vicarious lifelines. However, the functionality of vicarious memories varies among cultures. In Chinese participants the conjunction of vicarious and achievement memories serves a directive function. Although the directive function affirmed to be the gist of vicarious memories, in Russian participants they are relevant also to a self-reflective function. Accordingly, in Uzbek participants they are associated with a function of emotional regulation.
Keywords: autobiographical memory, vicarious memories, collectivism/individualism, lifeline, cross-cultural studies.